Frugal and Partial Heuristics as a Reference to Support Strategic Decisions - Tonelli, Dany Flávio; Antonialli, Luiz Marcelo (Revista Gestão da Produção Operações e Sistemas, 2007)
The objective of this paper was to discuss the construction and use of a heuristic referential as a tool to support strategic decisions. The heuristics, in this case, is similar to cognitive maps. The term frugal represents what is simple and the term partial refers to the reading of part of the aspects which influence the phenomenon. The adopted methodology was the study of cases of two technological innovations in the university context. The identification of critical factors led to the CPR (Culture, Processes and Resources) frugal and partial heuristic. The intention was to incorporate, into each of these spheres, characteristics that may interfere with such innovation processes and offer support to managers strategic decisions. It was concluded that, although the methodology of the heuristic generation xx presents important limitations, its use as a tool in specific contexts may be a way of awakening the inner cognitive experience. Keywords: Heuristic; Strategy; Case Study; Decision-making process.